COLLABORATIVE GOVERNANCE DALAM PENGAWASAN PERDAGANGAN SATWA ILEGAL: STUDI PADA BALAI KARANTINA HEWAN, IKAN, DAN TUMBUHAN LAMPUNG - Simarmata, Rahel Oktafariyanti; Sulistio, Eko Budi; Apandi, Apandi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
Collaborative Governance In Supervising Illegal Animal Trade: A Study At The Lampung Animal, Fish, And Plant Quarantine Center. This research is motivated by the high rate of illegal wildlife smuggling for trade. The Lampung Animal, Fish, and Plant Quarantine Agency plays a role in preventing illegal wildlife traffic. This study aims to determine how the Collaborative Governance process is carried out to reduce the number of wildlife smuggling in Lampung Province and to identify the obstacles faced. This study uses a qualitative method with a descriptive approach. The Ansell & Gash (2007) model is used as an analytical tool for this study with four main variables in collaboration, namely: Initial conditions, institutional design, facilitative leadership, and collaboration processes. The results of this study indicate that the Lampung Animal, Fish, and Plant Quarantine Agency has implemented Collaborative Governance with other government agencies, NGOs, the private sector, the expedition sector, and the community. The involvement of each sector is clearly visible in the field with the formation of a joint operations team that routinely patrols the Bakauheni port. There are inhibiting factors such as frequent overlap due to the lack of Standard Operating Procedures (SOPs) during patrols and a lack of competent human resources for supervision. This research is expected to provide input for the Lampung Animal, Fish and Plant Quarantine Center and other stakeholders.